The Transformasi of Zakat Towards a Green Economy: An Analysis of the Concept and Practice of Green Zakat - Amanda Laksmi; Nida Istiqomatus; Putri Nurul Izzati; Marcyano Awidi Bevan Alvaro; Amalia Nuril Hidayati (CV. ITTC INDONESIA, 2025)
Research findings indicate that the green economy focuses on improving social welfare by reducing environmental impact and using resources efficiently. Zakat can be a strategic tool to support sustainable development through productive and environmentally friendly programmes, in accordance with the principles of maqashid sharia. In addition, the role of the government, especially the Ministry of Finance, is very important in promoting green economic growth through tax policies, renewable energy support, forest management, and regional incentives. The combination of Islamic economics and the green economy is considered capable of strengthening sustainable development in Indonesia. This study uses a literature review method, which involves collecting and analysing secondary sources such as books, journals, and articles to obtain a theoretical basis and data to support the research. The discussion highlights that zakat has the potential to become a green economy instrument to support sustainable development. The integration of Islamic economics and the green economy is considered strategic because both emphasise sustainability, justice, and welfare. Through this research, it can be concluded that the transformation of zakat towards a green economy can strengthen sustainable development efforts in Indonesia. With the principles of justice and maintaining the purity of wealth, zakat and the green economy become a good collaboration for a sustainable economy.